The peculiarities of the haptic perception of the form and size of figures - Jovaiša , T.R. (Psichologija, 1981)
The haptic perception of six geometrical figures (triangle, quadrangle and pentagon) changing the object place during the experiments has been investigated. The subjects were told to draw perceived figures. 1,620 pictures of figures were obtained. From our experiment the following conclusions can be drawn: the area of the haptic space depends on (l) the complexity of the figure configuration, (2) the localization of the perceived figures in the space around the subjects, (3) the peculiarities of the subject's anthropometric hand structure.
Keywords: haptic perception; perception of figures